Testing Methods of Green Supply Chain, in Particular Supplier’s Selection an Evaluation Tools - Horváth, Adrienn (International Journal of Engineering and Management Sciences, 2018)
Today, more and more articles have emerged in the field of sustainability and sustainable development. Sustainability plays an important role in supply chain management too. Green Supply Chain Management (GSCM) has emerged as a key approach for enterprises seeking to make their businesses environmentally sustainable. The notion of GSCM implies the insertion of environmental criteria within the decision-making context of the traditional supply chain management. Enterprises are increasingly expected to extend their sustainability efforts beyond their own operations to their suppliers and customers to their sustainability expectations. Literature of green supplier evaluation and selection methods number is large, though the number of environmental factors are relatively limited. Recently in supply chain management decision making, approaches for evaluating green supplier performance have used both qualitative and quantitative environmental data. Given this evolving research area, the purpose of this article is to analyse research conducted in international scientific journals focusing on the selection and evaluation of a green supplier. The purpose of this article will answered two questions: Which selection methods are commonly used? What environmental and other selection criteria for green supplier management are popular?